Evaluating “English for Nusantara” for Grade 8: A Qualitative Content Analysis Based on Tomlinson’s Framework - Melisa, Kiki; Salmah; Ramadana, Nazila; Qamariah, Zaitun (Institut Agama ISlam Negeri Palangka Raya, 2024)
This study aims to evaluate the quality of the English for Nusantara textbook for eighth grade students based on Tomlinson's (2011) sixteen criteria for effective language learning materials. Using a qualitative content analysis method, the research focused specifically on one Chapters 0, 1, and 2 or one semester to examine the textbook's alignment with pedagogical principles such as learner engagement, authenticity, communicative purpose, and affective support. Data were collected using an evaluation rubric derived from Tomlinson's framework. The findings indicate that the textbook meets most of the criteria, particularly in terms of relevance, cultural integration, learner centered activities, and communicative input. However, the study also identifies areas for improvement, such as the inclusion of more authentic texts and differentiated tasks. Theoretically, this research contributes to the existing body of knowledge on effective language learning materials design by providing empirical evidence of how Tomlinson's principles manifest in government-issued textbooks. Practically, these results are expected to provide meaningful insights for educators, material developers, and policymakers in enhancing the design and use of English textbooks aligned with the Kurikulum Merdeka.